Application of an optimized dispersive nanomaterial ultrasound‐assisted microextraction method for preconcentration of carbofuran and propoxur and their determination by high‐performance liquid chromatography with UV detection. Issue 21 (18th September 2014) - Khodadoust, Saeid; Talebianpoor, Mohammad Sharif; Ghaedi, Mehrorang
<x xml:space="preserve">Abstract</x> An extraction method based on dispersive nanomaterial ultrasound‐assisted microextraction was used for the preconcentration of carbofuran and propoxur insecticides in water samples prior to high‐performance liquid chromatography with UV detection. ZnS:Ni nanoparticles were synthesized based on the reaction of the mixture of zinc acetate and nickel acetate with thioacetamide in aqueous media and then loaded on activated carbon (ZnS:Ni‐AC). Different methods were used for recognizing the properties of ZnS:Ni‐AC and then this nanomaterial was used for extraction of carbamate insecticide as new adsorbent. The influence of variables on the extraction method (such as amount of adsorbent (mg: NiZnS‐AC), pH and ionic strength of sample solution, vortex and ultrasonic time (min), ultrasound temperature and desorption volume (mL) was investigated by a screening 27–4 Plackett–Burman design. Then the significant variables were optimized by using a central composite design combined with a desirability function. At optimum conditions, this method had linear response >0.0060–10 μg/mL with detection limit 0.0015 μg/mL and relative standard deviations <5.0% (n = 3).